ANALISIS KEPUASAN KERJA KARYAWAN PADA PT ADITYA AGROINDO GROUP (KUALA HULU CENTRAL) KABUPATEN KETAPANG - Steven Steven; Angelina Fitria Rina Sari (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
Basically every company must attach importance to employee job satisfaction, this is done to achieve a target and the results desired by the company. The purpose of this study was to determine employee job satisfaction. The population in this study were employees of PT. Aditya Agroindo Group, totaling 96 people. While the sample method used in this study is saturated sampling or census. Saturated sampling or census is a sampling technique when all members of the population are sampled. Another term for saturated sampling is census. The result of this research is the level of job satisfaction of employees at PT. Aditya Agroindo Group Kualan Hulu Tengah is included in the satisfied category, this can be seen from the achievement of scores obtained from questionnaires distributed to employees